The Effectiveness Of Family Psychoeducation On The Ability Of Families To Care For Schizophrenia Patients - Putri, Sri Burhani (STIKes Alifah Padang, 2024)
Schizophrenia is a chronic mental disorder that requires long-term treatment, where the family plays an important role in patient care. Limited knowledge and ability of families in caring for schizophrenia patients is often a factor that worsens the patient's condition. Family psychoeducation is expected to improve the family's ability to care for patients, so that it can help prevent relapse and improve the patient's quality of life. This study aims to evaluate the effectiveness of the family psychoeducation program on improving the family's ability to care for schizophrenia patients, both in terms of knowledge, attitudes, and skills.This study used a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 50 families caring for schizophrenia patients, who were selected purposively. The psychoeducation program was given for 4 sessions with materials on schizophrenia knowledge, medication management, recognizing signs of relapse, and communication skills and emotional support. Measurement of family ability was carried out before and after the intervention using a validated questionnaire. The results showed a significant increase in family ability after being given psychoeducation (p <0.05). The average family knowledge score increased from 60% to 85%, skills in handling patients increased from 55% to 80%, and positive attitudes towards schizophrenia patients also increased. Psychoeducation has been shown to be effective in improving family skills, especially in terms of medication management and recognizing signs of relapse. The family psychoeducation program is effective in improving family skills in caring for schizophrenia patients. With increased family knowledge, attitudes, and skills, it is hoped that schizophrenia patients can receive better care at home, which can ultimately help prevent relapse and improve the patient's quality of life. This program needs to be implemented sustainably as part of community interventions in mental health services.